(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2025)
In his essay La letteratura circostante Simonetti identifies in speed the predominant formal aspect of contemporary Italian novel. A case in point is Ammaniti’s Che la festa cominci, which is strongly influenced by the rhythm of Hollywoodian film editing, translating movie’s structure in the novel through the parataxis and the plot. The paper wants to study the rhythm of Ammaniti’s narration through one of the most famous screenplay manuals: Snyder’s Save the Cat. The paper aims to compare this type of narration with Lahiri’s In altre parole. This autobiographical translingual novel narrates the encounter and learning path with Italian language of the protagonist /narrator. We intend to question the links between an Italian author who searches his narrative models in the Hollywood cinema, repudiating the Italian literary tradition, and a translingual writer who fulfills the opposite path: she abandons American form and language to write in a minor literature.